Раскопки в портовой части средневековой Сугдеи в 2007 г. - Майко, В.В.; Джанов, А.В.; Фарбей, А.М. (Археологічні дослідження в Україні, 2009)
The results of the excavations of a dwelling at the south-western area of the port part of Sugdea are published in the paper. On the floor of the house in the burnt layer a ceramic assemblage, not known before and containing white clay miniature vessels, was found. By the numismatic material the destruction of the house is dated back to the first half of the 13th c.